Comparative lipidomics and proteomics analysis of platelet lipid rafts using different detergents. (2nd October 2016) - Rabani, Vahideh; Davani, Siamak; Gambert-Nicot, Ségolène; Meneveau, Nicolas; Montange, Damien
Abstract: Lipid rafts play a pivotal role in physiological functions of platelets. Their isolation using nonionic mild detergents is considered as the gold standard method, but there is no consensual detergent for lipid raft studies. We aimed to investigate which detergent is the most suitable for lipid raft isolation from platelet membrane, based on lipidomics and proteomics analysis. Platelets were obtained from healthy donors. Twelve sucrose fractions were extracted by three different detergents, namely Brij 35, Lubrol WX, and Triton X100, at 0.05% and 1%. After lipidomics analysis and determination of fractions enriched in cholesterol (Ch) and sphingomyelin (SM), proteomics analysis was performed. Lipid rafts were mainly observed in 1–4 fractions, and non-rafts were distributed on 5–12 fractions. Considering the concentration of Ch and SM, Lubrol WX 1% and Triton X100 1% were more suitable detergents as they were able to isolate lipid raft fractions that were more enriched than non-raft fractions. By proteomics analysis, overall, 822 proteins were identified in platelet membrane. Lipid raft fractions isolated with Lubrol WX 0.05% and Triton X100 1% contained mainly plasma membrane proteins. However, only Lubrol WX 0.05 and 1% and Triton X100 1% were able to extract non-denaturing proteins with more than 10 transmembrane domains. Our results suggest that Triton X100 1% is the most suitable detergent for global lipid and protein studies on platelet plasma membrane. However, the detergent should be adapted if investigation of an association between specific proteins and lipid rafts is planned.